Contingencies of Self-worth and its Impact on Mental Health and Cognitive Vulnerability among undergraduate medical students: A Cross-Sectional Study - Rizwan, Ayesha; Noor ul Ain (Students’ Supplement of Journal of Rawalpindi Medical College, 2024)
Introduction: In social psychology, it’s well established that people strive to maintain and enhance their self-esteem. The contingencies of self-worth refer to the seven domains where individuals primarily invest their self-esteem: Academics, Appearance, Approval from others, Competition, Family Support, God’s Love, and Virtue. People aim to achieve success and avoid failure in these areas, as they are deeply invested in maintaining a positive self-image. Objective: To study the Contingencies of Self-worth among undergraduates Materials and Method: A Cross-sectional (Descriptive), Survey-based Study was conducted from the 18th of July to the 7th of September 2022 on uundergraduates of Riphah International University. A sample size of 378 was determined out of which 69 males and 309 females participated. The data was collected using questionnaires with Cronbach’s alpha values of .862 and .798 respectively. Result: Dependency of self-worth in undergraduates was seen to be highly dependent on these domains. It was seen that appearance had a positive correlation with body image dissatisfaction (r 0.155, p<-0.05). While Approval from others had a negative correlation with Competition (r -0.352, p<0.05), Decision making (r -0.330, p<0.05), Challenging (r -0.492, p<0.05), Body image satisfaction (r -0.431, p<0.05), and Contention in life (r -0.288, p<0.05), as well as with Psychiatric disorders (r 0.111, p<0.01). Family Support had a positive correlation with Contention in life (r 0.153, p<0.050). God’s love also had a positive correlation with contention in life (r 0.217, p<0.05) and a negative correlation with psychiatric disorders (r -10.139, p<0.05) Conclusion: Dependency of self-worth based on one’s appearance and approval from others had delirious impacts on the personality of an individual and it led to body image dissatisfaction, pessimism, and psychiatric disorders mainly depression, anxiety, and social phobia. However, those with strong religious beliefs were least likely to suffer from psychiatric disorders.